Perancangan dan Pengembangan Website Bisnis Digital untuk UMKM Kuliner - Zulfikar Zulfikar (Jurnal Sains dan Ilmu Terapan, 2024)
Digitalization of Micro, Small, and Medium Enterprises (MSMEs) is a crucial necessity for enhancing competitiveness and operational efficiency. However, many MSMEs still face various challenges in adopting digital technologies, particularly in marketing and operational management. This research aims to design and develop a digital business website for Ayam Geprek Mama as a case study in the implementation of technology-based systems. The methodology employed in this study is the Agile approach, which involves iterative phases of planning, development, testing, and implementation. The website is developed using PHP and MySQL for the backend, and HTML, CSS, and JavaScript for the frontend. This system is designed to facilitate the ordering process, marketing, and business management through an online ordering feature integrated with WhatsApp, menu information, and a product management system. Evaluation results indicate that the implementation of this website can enhance marketing reach, expedite the ordering process, and improve operational efficiency. With this digital solution, Ayam Geprek Mama can become more competitive in the culinary industry.